X intercept is where x=0
y intercept is where y=0
Answer:
110 pages
Step-by-step explanation:
Day 1 =x
Day 2 =2x
Day 3 =x-6
(x)+(2x)+(x-6)=458
Add likes together.
4x-6=458
4x=464. Divide both sides by 4 to get x. X=116
Day 3=116-6=110
Answer:
x = 9cm
Step-by-step explanation:
This is a right triangle so we can use the Pythagorean theorem
a^2 + b^2 = c^2 where a and b are the legs and c is the hypotenuse
6^2 + x^2 = ( sqrt(117) ^2)
36 + x^2 = 117
Subtract 36 from each side
x^2 = 117 -36
x^2 = 81
Take the square root of each side
sqrt(x^2) = sqrt(81)
x = 9
Hey there!
Let's break this expression into two parts:
6(3x-1) and -10x
To solve the first part, we need to use the distributive property which states:
a(b+c) = ab+ac
Applying that to this problem, we have:
6(3x) + 6(-1) =
18x - 6
Now, we can take that -10x and put it right back in:
18x - 6 - 10x
Combine like terms and subtract the 10x from the 18x to get:
8x - 6
Hope this helps!
Let <em>a</em> and <em>b</em> be the two numbers. Then
<em>a</em> + <em>b</em> = -4
<em>a b</em> = -2
Solve the second equation for <em>b</em> :
<em>b</em> = -2/<em>a</em>
Substitute this into the first equation:
<em>a</em> - 2/<em>a</em> = -4
Multiply both sides by <em>a</em> :
<em>a</em>² - 2 = -4<em>a</em>
Move 4<em>a</em> to the left side:
<em>a</em>² + 4<em>a</em> - 2 = 0
Use the quadratic formula to solve for <em>a</em> :
<em>a</em> = (-4 ± √(4² - 4(-2))) / 2
<em>a</em> = -2 ± √6
If <em>a</em> = -2 + √6, then
-2 + √6 + <em>b</em> = -4
<em>b</em> = -2 - √6
In the other case, we end up with the same numbers, but <em>a</em> and <em>b</em> are swapped.